Residual posttraumatic stress disorder symptoms after provision of brief behavioral intervention in low‐ and middle‐income countries: An individual‐patient data meta‐analysis. Issue 1 (9th November 2021) - Akhtar, Aemal; Koyiet, Phiona; Rahman, Atif; Schafer, Alison; Hamdani, Syed Usman; Cuijpers, Pim; Sijbrandij, Marit; Bryant, Richard A.
Abstract: Background: To address shortages of mental health specialists in low‐ and middle‐income countries, task‐shifting approaches have been employed to train nonspecialists to deliver evidence‐based scalable psychosocial interventions. Problem Management Plus (PM+) is a brief transdiagnostic nontrauma focused intervention for people affected by adversity. This study reports on the capacity of PM+ to address specific symptoms of posttraumatic stress disorder (PTSD). Methods: Individual patient data from three randomised controlled trials were combined and analysed to observe the impacts of PM+ ( n = 738) or enhanced treatment as usual (ETAU) ( n = 742) interventions on specific PTSD symptoms at posttreatment and 3‐month follow‐up. The PTSD‐Checklist for DSM‐5 (PCL‐5) was used to index PTSD symptoms, and presence of each symptom was defined as moderate severity (score ≥ 2 on individual items). Results: The average PCL‐5 score at baseline was 26.1 (SD: 16.8) with 463 (31.3%) scoring above 33, indicative of a diagnosis of PTSD. Following intervention, 12.5% and 5.8% of participants retained a score greater than 33 at postassessment and follow‐up, respectively. There was greater symptom reduction for PM+ than for ETAU for most symptoms. Hyperarousal symptoms were the most common residual symptoms after PM+, with more than 30% of participants reporting persistent sleep disturbance, concentration difficulties, and anger. Conclusion: PM+ led to greater reduction in symptoms relating to re‐experiencing and avoidance. The evidence indicates that strategies focusing on hyperarousal symptoms including sleep, concentration, and anger difficulties, could be strengthened in this brief intervention.